Negara Islam ala Indonesia: Pemikiran Perti di Konstituante, 1956-1959 - Sandy Kurniawan; Abd. Rahman Hamid; Uswatun Hasanah (Universitas Hamzanwadi, 2025)
This article intends to discuss the thoughts of Persatuan Tarbiyah Islamiyah regarding the foundation of the Islamic state of Indonesia in the Constituent Assembly during 1956–1959, using a historical research method consisting of four stages: heuristics, source criticism, interpretation, and historiography. The sources used include Constituent Assembly archival documents obtained from the National Archives of the Republic of Indonesia, the National Library of the Republic of Indonesia, and the official website of the People’s Consultative Assembly of the Republic of Indonesia (MPR RI). The research results show that debates in the Constituent Assembly were dominated by ideological struggles among three main groups: supporters of the Islamic state foundation, Pancasila, and socio-economic foundations. In the forum, Persatuan Tarbiyah Islamiyah voiced ideas about an Islamic state foundation based on the Ahlussunnah Wal Jama’ah doctrine, with the implementation of Sharia and worship following the Imam Shafi’i school of thought. The concept of the Islamic state proposed by PERTI is not identical to the Islamic state model of Saudi Arabia. PERTI proposed a concept of the Islamic state that guarantees the welfare of society and upholds the values of tolerance in accordance with the characteristics of Indonesia as a multicultural nation.